Students’ conceptions and experiences of web 2.0 tools (2011)
Purpose – This paper aims to present the results of a study that investigated the Erasmus Mundus Digital Library Learning (DILL) Master programme students’ conceptions and experiences of the use of Web 2.0 tools. Design/methodology/approach – The study adopted phenomenography as a research approach to identify DILL students’ conceptions and experiences of Web 2.0 tools. Semi-structured interviews with open-ended questions were conducted with 12 students from Africa and Asia within the DILL Master programme. Findings – The data analysis revealed four categories of descriptions of Web 2.0 tools: communication, educational, professional and multi-purpose. For each category of descriptions preferred Web 2.0 tools were identified. Research limitations/implications – The study analyses only conceptions and experiences of the use of Web 2.0 tools of 12 DILL students. This small group of students was from Africa and Asia and, therefore, the results should not be generalized to describe all DILL students’ conceptions and experiences of the use of Web 2.0 tools. Practical implications – The results of this study can be taken into consideration when designing and delivering a DILL programme. In order to use technologies to support learning there is a need to understand and know what students do with these new technological tools. Originality/value – This paper supports the idea of integration of information and communication technologies into education and highlights the potential of Web 2.0 tools to support teaching and learning in the higher education setting.